Urgensi Aspek Psikologis pada Pemeriksaan Dispensasi Kawin Perspektif Maqāṣid al-Syarīʿah - Alwi, Bashori; Hudaifa Muslihatul Ummah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to determine the extent to which psychological aspects should be involved in judges' decisions and how maqosid sharia can be the basis for how important psychological aspects are in examining marriage dispensation. This research uses a normative approach method by reviewing the results of previous researchers and analyzing using the maqosid shari'ah approach. The results of this study indicate that the psychological aspect must have a vital role to determine the mental and emotional readiness of underage brides and grooms who are often undetectable through a purely legal approach. From the perspective of maqāṣid al-syarīʿah, a competent psychological examination (conducted by experts) serves as an effort to protect the soul (ḥifẓ an-nafs), intellect (ḥifẓ al-aql) and offspring (ḥifẓ an-nasl) and can prevent potential long-term negative impacts such as divorce, trauma or mental health problems. A competent psychological assessment also contributes significantly to ensuring that early marriage can only take place in a genuine emergency in accordance with the interests of the child. This assessment also recommends strengthening regulations that require psychological assessments as an integral part of the marriage dispensation procedure in order to create fair and accountable judge decisions.